PENGEMBANGAN TUTORIAL BOOK DALAM PEMBELAJARAN FOTOGRAFI BAGI ANAK TUNARUNGU DI SMKN 4 PADANG - Dina Permatasari (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: This research is motivated by problems that researchers found in 4 SMK Padang. Where not optimal use of the media as well as the appropriate method of learning photography for deaf children. This study uses a Research and Development. The results of this study indicate, that the successful development of a tutorial book on learning photography for deaf children. Suggestions in the course of a study is that teachers can use the book tutorials provide photographic materials for deaf students Kata kunci: Anak Tunarungu; Pembelajaran Fotografi; Tutorial Book.